Immersed in the realm of possibility: An encounter with digital technologies in early childhood education - Stojković Jelena (Nastava i Vaspitanje)
In the complex and multifaceted world we live in, contemporary theories promote education as a space for encounters and building of different, affirmative, and constructive relationships. In this paper, we start from the question of what and whom we are educating in the current moment, examining these through poststructuralist and posthumanist ideas and concepts, along with an example of an encounter with digital technologies in early childhood education. In this way, we aim to explore the outlines of early childhood education that materially and discursively fall outside predefined (and humanistic) frameworks, as well as the potentials that remain overshadowed by dominant understandings and practices of using digital technologies. Posthumanist thinking about early childhood education as an encounter with beings, processes, things, and ideas, opens up a space for a different consideration of proximity, sensitivity, and unpredictability. Alongside meaningfulness, purposefulness, and a critical stance, these are the key values on which the use of digital technologies in early childhood education can be established. The research has shown that unexpected encounters with digital technologies in early childhood education can indicate a building capacity to respond collectively and be responsible. However, there is a strong need for critical positioning and further exploration of posthumanist ideas and concepts, especially in the light of understanding education as an ethical practice.